2008
DOI: 10.1080/10428190802475295
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin shows anticancer activity in primary chronic lymphocytic leukemia cellsin vitro, as single agent and in drug combination

Abstract: The mammalian target of rapamycin inhibitor rapamycin and its analogues show promising anticancer activity in various experimental tumor models and are presently evaluated in clinical trials. We, here, evaluated the in vitro activity of rapamycin with regard to tumor-type specificity and possible mechanisms of drug resistance in 97 tumor cell samples from patients and in a resistance-based cell line panel, using the fluorometric microculture cytotoxicity assay. Rapamycin was dose-dependently cytotoxic in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Combining rapamycin with chemotherapy, for example, completely bypasses AKT's ability to promote chemotherapy resistance in mouse lymphoma models [11,12]. Studies in cell lines and primary tumor cells in vitro also provide support for rapalog-chemotherapy combinations [43,44]. There are now several trials planned or underway for NHL patients combining chemotherapy agents with the rapalogs, including adding temsirolimus to rituximab (R) and bendamustine for relapsed follicular lymphoma; temsirolimus plus R-cladribine for previously untreated MCL; everolimus plus CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) for peripheral Tcell lymphoma; and a randomized, placebo-controlled assessment of everolimus as an adjuvant post R-CHOP for DLBCL (Table 2).…”
Section: Looking Ahead: New Combinations New Drugs New Approachesmentioning
confidence: 93%
“…Combining rapamycin with chemotherapy, for example, completely bypasses AKT's ability to promote chemotherapy resistance in mouse lymphoma models [11,12]. Studies in cell lines and primary tumor cells in vitro also provide support for rapalog-chemotherapy combinations [43,44]. There are now several trials planned or underway for NHL patients combining chemotherapy agents with the rapalogs, including adding temsirolimus to rituximab (R) and bendamustine for relapsed follicular lymphoma; temsirolimus plus R-cladribine for previously untreated MCL; everolimus plus CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) for peripheral Tcell lymphoma; and a randomized, placebo-controlled assessment of everolimus as an adjuvant post R-CHOP for DLBCL (Table 2).…”
Section: Looking Ahead: New Combinations New Drugs New Approachesmentioning
confidence: 93%
“…Furthermore, other studies recently reported a pro-apoptotic effect of rapamycin in primary B-CLL cells, thereby emphasizing the therapeutic value of mTOR inhibition in this disease. 90,91 Finally, Zanesi and colleagues showed the ability of rapamycin to improve survival of CLL transgenic mouse. 92 Given these results, clinical trials are ongoing in CLL and results from two phase II clinical trials have been recently published.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…However, single-isoform inhibitors against PI3Ka/b/d and pan-class-1 PI3K inhibitors in CLL cells have all been reported to induce apoptosis. 22,23 Pharmacologic inhibition of mTOR induces cell cycle arrest and apoptosis in CLL cells [24][25][26] ; however, prolonged inhibition of mTOR is known to disrupt negative feedback loops and cause increased AKT S473 activation in other malignancies. 27,28 Given the important role of both PI3K and mTOR in CLL cell survival, the dual pharmacologic inhibition of both class-1 PI3K and mTOR signaling may offer new therapeutic potential, with the possibility of deeper remissions or as an alternative after resistance to idelalisib.…”
Section: Cd19mentioning
confidence: 99%